Reinvigorating A City Through Water Conservation: Review of Literature - Hussain, Nor Hayati; Samynathan, Kadhiraven (MAJ - Malaysia Architectural Journal, 2025)
This paper investigates the pivotal role of water conservation in revitalizing urban landscapes and enhancing community well-being. The lack of appreciation and awareness of water conservation in accessible urban blue spaces, like rivers or parks, hampers well-being and limits opportunities. This paper addresses the historical trajectory of water-centric infrastructure, the integration of water elements into architectural designs, and water accessibility in improving urban life quality and driving economic progress. It employs a systematic review that draws upon a broad array of peer-reviewed sources from urban planning, architecture, environmental science, and sociology using the Scopus online database, curated on July 10th, 2023. The culmination of this exploration yields invaluable insights and actionable recommendations, offering a nuanced understanding of the intricate interplay between water conservation and the urban community fabric. These findings are poised to significantly influence urban planning and policy decisions, fostering a vision for harmonious, sustainable, and thriving cities equipped to navigate future challenges with resilience and foresight.